The Features of the Stylistic use of Some Phraseologisms with the Sound (Phonetic) Harmony in the Karakalpak Language - Yusupova Biybisanem Turdıbaevna (International Journal on Orange Technologies, 2021)
The article deals with the adaptation of some phraseologies in the Karakalpak language to the types of style, the peculiarities of their use in the spoken language and the style of fiction, stylistic services in portraiture, the expression of nature phenomena, human emotions.